Immunological Mechanisms and Effects of Bacterial Infections in Acute-on-Chronic Liver Failure - Sumeng Li; Jing Liu; Jun Wu; Xin Zheng (Cells)
Acute-on-chronic liver failure (ACLF) is a severe clinical syndrome characterized by high morbidity and mortality rates. Bacterial infection is a frequent precipitating factor and complication in ACLF patients, significantly worsening patient outcomes. Elucidating the mechanisms underlying bacterial infections and their impact on ACLF pathophysiology is crucial for developing effective therapies to reduce infection rates and mortality. Current research highlights that immune suppression in ACLF increases susceptibility to bacterial infections, which in turn exacerbate immune dysfunction. However, a comprehensive review summarizing the emerging mechanisms underlying this immunosuppression is currently lacking. This review aims to provide an overview of the latest research, focusing on alterations in the immune responses of innate immune cells—including monocytes, macrophages, and neutrophils—as well as adaptive immune cells such as T and B lymphocytes during the onset and progression of bacterial infections in ACLF. In addition, recent advances in immunomodulatory therapies, including stem cell-based interventions, will also be discussed.